Low-coherence enhanced backscattering for depth-selective tissue measurement. - Winarni Maria Magdalena. (2011)
Optical technique is a powerful tool for cancer diagnosis, as there are many optical contrasts that can be utilized to differentiate cancer lesion. One potential non-invasive optical measurement of cancer is Coherent Backscattering (CBS) or is also known as Enhanced Backscattering (EBS). It is a photon self-interference effect, which shows an increase of the intensity in the backward direction, creating a cone shape intensity profile with sharp peak. The information of optical properties such as transport mean free path length (ℓ*) can be inferred from the cone shape. However, application of CBS in biological media is hindered by some challenges, which causes difficult observation especially on stratified tissue. This project focused on utilization of low-coherence light source in CBS phenomena, creating the term Low-coherence Enhanced Backscattering (LEBS), to improve the observation in biological media which has higher ℓ* as weakly scattering medium. Experiment with milk and intralipid shows the important dependency of LEBS signal to the spatial coherence length Lsc. Low-coherence illumination acts as spatial filter to limit the radius of photon penetration to the spatial coherence length and thus allows depth-selective measurement. From analysis of the radial intensity distribution, this project verifies that maximum penetration depth is less than Lsc for three different Lsc used (11, 17, and 34μm). Hence, LEBS method has a potential to examine different layer of tissues, in particular the epithelial layer where cancers usually proliferates, by selecting appropriate Lsc for desired penetration depth.